Josquin des Prez and his musical legacy : an introductory guide - Elders, Willem (Leuven University Press, 2013)
Josquin des Prez and His Musical Legacy' is the most up-to-date contribution to the research on one of the most important and internationally famous composers of the Renaissance. This monograph offers factual information on the composer as well as insights into his 16th-century and modern reception, a survey of the sources of his music, and a discussion of the thorny issue of authorship. Willem Elders, one of the most distinguished scholars of Josquin's music, also discusses the influence of Gregorian chant as a source of inspiration and explains the various aspects of Josquin's symbolic language. Each individual work (including some of those in the old Josquin edition now considered inauthentic) receives a short discussion of relevant contextual aspects and interesting musical features. Ranges and lengths are given for each work. The style is adapted to the professional musicologist as well as to the music lover' and performer.